Climate change accounting and disclosure: A systematic literature review - Aisa Tri Agustini; Choirunnisa Arifa (The Indonesian Accounting Review, 2024)
This study aims to explore the conceptual structure and evolution of accounting literature related to climate change accounting and disclosure. This study uses a systematic literature review (SLR) assisted by Bibliometric and NVivo tools to answer research questions through five stages and fulfill the requirements set out in the SLR. From the selection results, the sample used is 49 articles for the period of 2009 - 2022 obtained from the Scopus database. Climate change accounting is largely disclosed with a focus on reducing carbon emissions. Meanwhile, other areas such as financial impacts that are in line with IFRS directives are still rarely disclosed and researched. Theoretically, companies adapt and disclose climate change accounting because of internal and external incentives. Disclosure also reveals information regarding the company’s adaptive capacity to climate change risks. The results of this study indicte that the climate change accounting disclosure have not been standardized. Therefore, it is recommended that the government or related agencies consider standardizing the disclosure of adaptive actions related to climate change.